Risk factors for cancellation after dispatch of rapid response cars for prehospital emergency care: a single‐center, case–control study. Issue 1 (26th July 2021) - Inoue, Juri; Hirano, Yohei; Fukumoto, Yuichi; Kudo, Tomohiro; Usami, Ryo; Kondo, Yutaka; Matsuda, Shigeru; Okamoto, Ken; Tanaka, Hiroshi
Abstract: Aim: The objective of this study is to identify the risk factors for cancellation after dispatch of rapid response cars (RRC) for prehospital emergency care. Methods: We retrospectively extracted data from all RRC cases dispatched from our hospital between April 2017 and March 2019. A total of 1, 440 cases were included in our study and divided into either the "cancelled" group ( n  = 723) or the "treated" group ( n  = 717), based on the occurrence of cancellation. The variables obtained from the request calls for RRC included patient characteristics, distance from the hospital to the scene, and reasons for RRC request. The variables were compared between the two groups and logistic regression analysis was carried out to identify the risk factors for RRC cancellation. Results: Multivariable analysis showed that distance from the hospital to the scene (odds ratio [OR] 1.25; 95% confidence interval (CI), 1.21–1.28), suspicion of cardiopulmonary arrest with no witness information (OR 7.61; 95% CI, 4.13–14.00), dyspnea (OR 2.22; 95% CI, 1.19–4.11), and suicide by hanging (OR 3.49; 95% CI, 1.37–8.89) were independent risk factors for cancellation. Conclusions: In our study, a greater distance from the hospital to the scene, suspicion of cardiopulmonary arrest with no witness information, dyspnea, and suicide by hanging were identified as independent risk factors for cancellation after dispatch of RRC. Evaluating the risk factors for cancellation at individual facilities could help hospitals adjust their dispatch criteria to allocate limited medical resources more effectively. Abstract : Our study suggests that the greater distance from the hospital to the scene, suspicion of cardiopulmonary arrest with no witness information, dyspnea, and suicide by hanging are the independent risk factors for cancellation after dispatch of rapid response cars.